Pengembangan Media Smart Box Literasi untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas II Sekolah Dasar - Lunissa Prasdiana Putri; Karimatus Saidah; Frans Aditia Wiguna (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Early reading instruction for Grade IIA students at MIS Al Irsyad Al Islamiyyah, Kediri City, has not been optimal due to a teacher-centered approach and limited use of instructional media. This study aims to determine the validity, practicality, and effectiveness of the "Literacy Smart Box" instructional medium for teaching new vocabulary. The study employs the Research and Development (R&D) method using the ADDIE model. The research subjects consisted of 36 students: 10 in the limited trial and 26 in the field trial. Data were collected through observation, interviews, questionnaires, and tests, then analyzed using percentages and a paired-sample t-test. The results indicate that the medium achieved a validity level of 81.5% (highly valid) and a practicality level of 94% (highly practical). It also improved early reading skills, with the average score rising from 67.50 in the pre-test to 89.62 in the post-test. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05), demonstrating a significant improvement in early reading skills. All students achieved learning mastery. Thus, the Literacy Smart Box meets the criteria of being highly valid, highly practical, and highly effective, making it suitable for use as an instructional medium for early reading. This medium offers an engaging alternative for helping students learn new vocabulary and improve their early reading abilities.